L‐selectin shedding by NSAIDs: Old friends in new dresses. Issue 1 (16th January 2013) - Zarbock, Alexander; Rossaint, Jan
<x xml:space="preserve">Abstract</x> The recruitment of leukocytes to sites of inflammation requires the highly organized interplay of cell adhesion molecules on both leukocytes and inflamed endothelial cells, and disrupting the interaction of these molecules may compromise efficient recruitment of immune cells. Non‐steroidal anti‐inflammatory drugs inhibit inflammatory responses by several mechanisms including inhibition of prostaglandin synthesis and decreasing the expression of cell surface adhesion molecules. A report by Herrera‐Garcia et al. [Eur. J. Immunol. 2013. 43: 55–64] in this issue of the European Journal of Immunology shows that the non‐steroidal anti‐inflammatory drug N‐phenylanthranilic acid (N‐Ph) causes L‐selectin to be shed from the leukocyte plasma membrane and that this process in turn causes a decrease in leukocyte recruitment during inflammation in vivo. This finding may lead to novel approaches using N‐Ph in the control of inflammatory processes as discussed in this Commentary.